2023
DOI: 10.1002/anie.202308420
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Color‐Tunable Long Persistent Luminescence in Cs2CdCl4 Ruddlesden‐Popper Phase Perovskites

Abstract: Two‐dimensional (2D)‐halide perovskites have been enriched over recent years to offer remarkable features from diverse chemical structures and environmental stability endowed with exciting functionalities in photoelectric detectors and phosphorescence systems. However, the low conversion efficiency of singlet to triplet in 2D hybrid halide perovskites reduces phosphorescence lifetimes. In this study, the long persistent luminescence of 2D all‐inorganic perovskites with a self‐assembled 2D interlayer galleries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Inorganic luminescent crystals have garnered significant attention in recent years due to their remarkable optoelectronic properties and potential applications in lighting and display technologies. 1–5 In particular, inorganic perovskite luminescent materials have sparked widespread interest due to their unique properties such as high photoluminescence efficiency, tunable bandgap, and excellent charge transport characteristics. 3–5 However, there is a crucial need to explore new materials that are non-toxic and abundant, considering the environmental and health concerns associated with the commonly used toxic lead (Pb) and cadmium (Cd) containing materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic luminescent crystals have garnered significant attention in recent years due to their remarkable optoelectronic properties and potential applications in lighting and display technologies. 1–5 In particular, inorganic perovskite luminescent materials have sparked widespread interest due to their unique properties such as high photoluminescence efficiency, tunable bandgap, and excellent charge transport characteristics. 3–5 However, there is a crucial need to explore new materials that are non-toxic and abundant, considering the environmental and health concerns associated with the commonly used toxic lead (Pb) and cadmium (Cd) containing materials.…”
Section: Introductionmentioning
confidence: 99%
“…1–5 In particular, inorganic perovskite luminescent materials have sparked widespread interest due to their unique properties such as high photoluminescence efficiency, tunable bandgap, and excellent charge transport characteristics. 3–5 However, there is a crucial need to explore new materials that are non-toxic and abundant, considering the environmental and health concerns associated with the commonly used toxic lead (Pb) and cadmium (Cd) containing materials. 6–20 This has motivated researchers to investigate alternative materials that offer both efficient luminescence and reduced toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…perovskite nanocrystals with a temperature-independent emission from 298 to 373 K. 10 The fluorine-rich shell was purported to have a wider energy gap than the inner nanocrystal core, suppressing carrier trapping and improving thermal stability. 8,10 Han et al found that Mn 2+ -doped Rb 3 Cd 2 Cl 7 single crystals did not suffer from luminescence intensity quenching up to 423 K. 20,24,25 More recently, Zhou et al developed a Zr 4+ /Mn 2+ codoped CsCdCl 3 system featuring a robust anti-TQ radioluminescence up to 448 K, a record value for metal halide materials. 12 The authors hypothesized that the thermally stable radioluminescence was due to compensation of the emission losses at high temperatures by thermally activated energy transfer from defects to the Mn 2+ emitters.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12 However, even though anti-TQ metal halide perovskite phosphors have been intensely explored in the last three years, their anti-TQ behavior still lags behind that of the metal nitride/oxide-based phosphors. [10][11][12]20 More importantly, they are either Pbbased 10,11 or Cd-based hosts, 12,20,25,26 which are toxic.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, the exploration of all-inorganic halide perovskite crystals has gained significant attention due to their potential for applications, including lighting, displays, and sensing. However, the presence of toxic elements, such as Pb and Cd, in some known all-inorganic perovskite emitters has raised environmental and health concerns. Therefore, there is an imperative need to develop nontoxic alternatives with desirable luminescent properties.…”
Section: Introductionmentioning
confidence: 99%